PENGGUNAAN OBAT TRADISIONAL DAN PEMBUATAN SEDIAAN CELUP DAUN KELOR BAGI MASYARAKAT DI SAKO KECAMATAN LUBUK KILANGAN KOTA PADANG - Aldi, Yufri; Umar, Salman; Azukhruf, Wanda Sabila; Alianta, Aditya Alqamal (Jurnal Hilirisasi IPTEKS, 2024)
Moringa leaf (Moringa oleifera Lam.) is a traditional medicinal plant widely recognized in Indonesia and frequently utilised by the local community. Numerous studies have demonstrated its efficacy in boosting the immune system. In light of this, enhancing community awareness regarding the health benefits of Moringa leaves is essential. The objective of this initiative was to educate the community on how to process Moringa leaves accurately and appropriately, including proper dosage frequency based on the severity of illness and duration of use. This activity took place in Batu Gadang Village, Lubuk Kilangan District, specifically on Jl. Sako. Participants included 30 PKK Cadres and Bundo Kandung from the same area. The methodology involved educational lectures followed by hands-on training. The training focused on proper harvesting techniques and the preparation of Moringa leaf powder in accordance with traditional medicinal practices. A question-and-answer session was conducted to ensure participants fully grasped the material. The results indicated a high level of engagement, evidenced by active participation in both the Q&A and practical sessions. It can be concluded that the community now has a better understanding of the medicinal uses of Moringa leaves. Participants are encouraged to continue preparing Moringa leaf infusions to promote improved immunity.